POSSIBILITY OF APPLYING ECONOMIC VALUE ADDED IN THE CAPITAL MARKET OF THE REPUBLIC OF SRPSKA - Alihodžić, Almir (The European Journal of Applied Economics, 2013)
The efficiency of a management team primarily depends on the level of improvement of enterprise performances, i.e. whether its market value has increased or whether it creates value for shareholders. The accounting net profit can provide a partial answer to this question because it covers only one portion of the cost of capital, i.e. the cost of debt capital, while the price and cost of equity are disregarded. The method of the economic value added takes into account an average cost of capital, i.e. it calculates the total costs of borrowed capital and own capital. This paper explores the possibility to calculate economic value added for an individual share within the share market index of BIRS.